ANALISA PENGANGKUTAN TANDAN BUAH SEGAR DENGAN TEKNIK SPC (Statistical Process Control) - Dina Arfianti Saragih; Debby Sanandra; Washington Simbolon (Institut Teknologi Sawit Indonesia, 2019)
This study aims to determine the effectiveness of the Palm Oil Fresh Fruit Bunch transportation system. This research was conducted at Air Batu Estate Afdeling I PTPN IV, which is located in Asahan Regency, North Sumatra. This research was conducted in July to August 2018. The method used in this study was a descriptive method by taking data in the field about the arrangement of transportation of oil palm fresh fruit bunches. Observations made included information on the Air Batu estate, estimated daily harvest, transport transportation, daily production and transportation, and obstacles or obstacles to the transportation process. Based on observations made, it was found that: (1) The average loading process time for the rotation II was 64.22 minutes, the average time of the transport process from Afdeling I to PKS for the rotation II was 28.68 minutes, and the average time average unloading process at PKS is duration 18.30 minutes, (2) Based on the SPC for the value of Cp and Cpk for loading, transporting and unloading processing time can be said to be less effective with Cp and Cpk values <1, (3) Average number of trips per day in August 2018 which is 2 trips / day. The theoretical trip calculation results are 4 trips / day, (4) The average number of daily harvest production in August 2018 in Afdeling I of Batu Air Farm 34,542 kg TBS. Daily crop yields are still below the daily harvest planning target of 38,307 kg FFB, and (5) The speed of the truck is 12.6 km/hr, this is due to the damaged and bupy road.